2011
DOI: 10.1088/0964-1726/21/1/015015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a shape memory alloy wire actuator with a modulated adaptive controller for position control

Abstract: This paper presents an experimental investigation of position control of a shape memory alloy (SMA) wire actuator with adaptive and modulated adaptive controllers. The transfer function model of the SMA wire actuator is determined from the experimental open loop response. Adaptive controllers, namely LMS–GSPI, RLS–GSPI and Kalman–GSPI, and modulated adaptive controllers using pulse width modulation (PWM) are designed. The performances of these controllers are experimentally investigated for the position contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The experimental setup reported in [3] is used to conduct the open and closed loop performance in this work. The schematic of the experimental setup used to measure and control the SMA actuator is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup reported in [3] is used to conduct the open and closed loop performance in this work. The schematic of the experimental setup used to measure and control the SMA actuator is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, the control of SMA position or displacement is difficult due to its inherent properties such as nonlinearity, hysteresis. Different controllers have been developed to control the SMA actuator with position or displacement feedback and demonstrated a potential for SMA actuators to be used as motion control actuator [2][3][4][5]. The non-linearity and hysteresis of SMA actuator posed difficulties in expressing these behaviors in modeling the SMA actuator.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the SMA actuator changes during phase transformation and a fixed cylindrical geometry assumption cannot be used as in straight SMA wires. Bhattacharyya et al (2002) and Senthilkumar et al (2012) showed that temperature-current relation of SMA can be represented with an empirical relation: Tfalse(tfalse)=T+a1a2IRfalse(1-e-a2tfalse) where I is the current supplied to the SMA, R is the electrical resistance of the SMA, a 1 and a 2 are the parameters to be determined through experiments. The resistance change of the SMA actuator during phase transformation is less than 0.1 Ω and it is assumed to be constant.…”
Section: Methodsmentioning
confidence: 99%
“…This effect means that the material can recover to its original shape and undergo a transformation from parent or austenite phase to martensite phase. [37][38][39] Figure 1 presents the schematic of phase transition of the SMA dominated by heat and stress together. In 1981, Miyazaki et al found that the stress-strain curves of Ni-Ti alloys were significantly different based on different temperatures.…”
Section: Introductionmentioning
confidence: 99%